2015
DOI: 10.1007/s11042-014-2437-9
|View full text |Cite
|
Sign up to set email alerts
|

A user-centric evaluation of context-aware recommendations for a mobile news service

Abstract: Traditional recommender systems provide personal suggestions based on the user's preferences, without taking into account any additional contextual information, such as time or device type. The added value of contextual information for the recommendation process is highly dependent on the application domain, the type of contextual information, and variations in users' usage behavior in different contextual situations. This paper investigates whether users utilize a mobile news service in different contextual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…An accurate definition of recommender system, given by Burke [35], is ''any system that produces individualized recommendations as output or has the effect of guiding the user in a personalized way to interesting or useful objects in a large space of possible options''. Within recommender systems, various techniques can be distinguished based on the knowledge source [27]: demographic, knowledge-based, community-based, content-based, collaborative, and hybrid recommendations. Among them, we focus on CB.…”
Section: A Content-based Recommender Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…An accurate definition of recommender system, given by Burke [35], is ''any system that produces individualized recommendations as output or has the effect of guiding the user in a personalized way to interesting or useful objects in a large space of possible options''. Within recommender systems, various techniques can be distinguished based on the knowledge source [27]: demographic, knowledge-based, community-based, content-based, collaborative, and hybrid recommendations. Among them, we focus on CB.…”
Section: A Content-based Recommender Systemsmentioning
confidence: 99%
“…Here we focus on those CB that use a vector space modeling to represent items. With this regard there are CB with (i) feature-based representations, where items are usually stored in a database table where rows are items and columns are the item features [27], [36], [37]; and (ii) free-text representation, where there is a natural language piece of text that describes the item [38].…”
Section: A Content-based Recommender Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [61] proposed a light-weight mobile RS with semantic-rich awareness information, which is able to provide content recommendations that are tailored to learners' background, contexts and the task at hand. In [62], an assessment of the usefulness of contextual information with respect to classical RS was performed to determine users' utilization of mobile news services and how contextual information influences their consumption behavior. While [61] and [62] suggest new mechanisms in mobile RS, [63] report a framework designed for library staff to provide location-based access to information via mobile computing platform, which eases access and utilization of the library collection.…”
Section: (2) E-documents Domainmentioning
confidence: 99%
“…It is observed that only one or two contexts are incorporated by the researchers in the RS process such as in [62], and considering the dynamicity of users, incorporating a single context may not necessarily represent a user's interests and preferences.…”
Section: Recommendations and Future Research Directionsmentioning
confidence: 99%